Fountain house : creating community in mental health practice - Doyle, Alan.; Lanoil, Julius; Dudek, Kenneth J. (New York : Columbia University Press, 2013)
Since 1948, people suffering from mental health issues, mental health professionals, and committed volunteers have gathered at Fountain House in New York City to find relief from stigmatisation and social alienation. Its 'working community' approach has earned the organisation vast critical recognition, enabling it to replicate its methods across the world. This volume describes the humanity, social inclusivity, personal empowerment, and perpetual innovation of the Fountain House approach.
Cover; Title Page; Copyright; Dedication; Contents; Foreword; Introduction; Part I. Working Community; 1. Insights from Activity Group Therapy; 2. Reinventing Fountain House; 3. Core Principles of a Working Community; Part II. Social Practice; 4. Defining Social Practice; 5. Transformational Design; 6. Motivational Coaching; 7. Issues in Relationships; Afterword. A Place for Recovery in the Community; Acknowledgments; Chronology; Glossary; Notes; References; Index.
Print version record.
Includes bibliographical references and index.
English.
JSTOR
Keywords: Fountain House (New York, N.Y.); Fountain House (New York, N.Y.); Mentally ill -- Institutional care -- United States -- History; Mentally ill -- Rehabilitation -- New York (State) -- New York; Mentally ill -- Deinstitutionalization -- New York (State) -- New York; Community mental health services -- New York (State) -- New York -- History; Mental health services; Medical care; People with disabilities; National health services; Health facilities; Therapeutics; Deinstitutionalization; Mental illness; Community mental health services; Mentally ill women; Mental Health Services; Patient Care; Ambulatory Care Facilities; Psychiatry and Psychology; Community Health Services; Disabled Persons; Persons; Health Services; Behavioral Disciplines and Activities; Health Facilities; Therapeutics; Named Groups; Health Care Facilities, Manpower, and Services; Analytical, Diagnostic and Therapeutic Techniques and Equipment; Delivery of Health Care; Deinstitutionalization; Institutionalization; Mental Disorders; Community Mental Health Services; Community Mental Health Centers; Persons with Psychiatric Disorders; State Medicine; Personnes vivant avec un trouble de santé mentale -- Soins en institutions -- États-Unis -- Histoire; Personnes vivant avec un trouble de santé mentale -- Réadaptation -- New York (État) -- New York; Personnes vivant avec un trouble de santé mentale -- Désinstitutionnalisation -- New York (État) -- New York; Services communautaires de santé mentale -- New York (État) -- New York -- Histoire; Services de santé mentale; Soins médicaux.; Services de soins ambulatoires; Personnes handicapées.; Services de santé.; Équipements sanitaires; Thérapeutique.; Prestation de soins; Désinstitutionnalisation.; Maladies mentales; Services communautaires de santé mentale; Femmes vivant avec un trouble de santé mentale; handicapped; people with physical disabilities; health facilities; mental disorders; treating (health care function); people with psychiatric illnesses